Phase I study of azacitidine and bortezomib in adults with relapsed or refractory acute myeloid leukemia. Issue 6 (June 2014) - Walker, Alison R.; Klisovic, Rebecca B.; Garzon, Ramiro; Schaaf, Larry J.; Humphries, Kristina; Devine, Steven M.; Byrd, John C.; Grever, Michael R.; Marcucci, Guido; Blum, William
Abstract We previously reported that bortezomib indirectly modulates transcription of DNA methyltransferase 1 (DNMT). We designed a phase I study of azacitidine (a direct DNMT inhibitor) plus bortezomib in acute myeloid leukemia (AML) to determine safety and tolerability. Twenty-three adults with relapsed/refractory AML received azacitidine 75 mg/m2 daily on days 1–7. Bortezomib was dose escalated from 0.7 mg/m2 on days 2 and 5 to 1.3 mg/m2 on days 2, 5, 9 and 12. The target dose was reached without dose limiting toxicities. Infection and/or febrile neutropenia were frequent. Patients received a median of 2 cycles of therapy (range, 1–12+). Five of 23 patients achieved remission, including two with morphologic and cytogenetic complete response (CR) and three with CR and incomplete count recovery (CRi). Of CR/CRi responders with cytogenetic abnormalities at baseline, three of four achieved cytogenetic CR. The combination of azacitidine and bortezomib was tolerable and active in this cohort of poor-risk previously treated patients with AML.